Innovation Of Interactive Multimedia In Efforts To Increase Creativity And Sociology Learning Outcomes For Class Xi Ips 5 At Sma N 1 Pasaman - Prima, Ossy Ana; Anwar, Syafri (Master Program of Social Science Education of Universitas Negeri Padang, Indonesia, 2022)
This research was structured with the aim of students' creativity and learning outcomes using interactive multimedia innovations for class XI IPS 5 SMAN 1 Pasaman, Academic Year 2021/2021. Creativity and learning outcomes are referred to in this study, namely the ability of students to provide an active and creative attitude in learning and the bias to give good learning outcomes during the implementation of learning. The type of this research is Classroom Action Research (CAR), in which the teacher is the implementer of learning as well as the researcher. This research design uses a model. This research was carried out in the even semester of the 2019/2020 school year, namely in March. The subjects of this study were students of class XI IPS 5 consisting of 34 students. The object of research is the creativity and learning outcomes of students. Data collection techniques using observation and interviews. Data were analyzed descriptively and presented in tabular form. The results showed an increase in students' creativity and learning outcomes, namely in the first cycle. In the first cycle, students' learning mastery increased by 70.58% (initial condition 8.82% increased to 70.58%). In the second cycle, with the improvement and modification of learning multimedia, accompanied by the management of group formation and the provision of rewards, student learning outcomes increased by 88.23% (the condition of the first cycle increased 70.58% to 88.23%). Learning achievement in cycle II has met the indicators of success because 75% of students have reached the KKM. Data were analyzed descriptively and presented in tabular form. The results showed an increase in students' creativity and learning outcomes, namely in the first cycle. In the first cycle, students' learning mastery increased by 70.58% (initial condition 8.82% increased to 70.58%). In the second cycle, with the improvement and modification of learning multimedia, accompanied by group formation management and giving rewards, student learning outcomes increased by 88.23% (the condition of the first cycle increased 70.58% to 88.23%). Learning achievement in cycle II has met the indicators of success because 75% of students have reached the KKM. Data were analyzed descriptively and presented in tabular form. The results showed an increase in students' creativity and learning outcomes, namely in the first cycle. In the first cycle, students' learning mastery increased by 70.58% (initial condition 8.82% increased to 70.58%). In the second cycle, with the improvement and modification of learning multimedia, accompanied by the management of group formation and the provision of rewards, student learning outcomes increased by 88.23% (the condition of the first cycle increased 70.58% to 88.23%). Learning achievement in cycle II has met the indicators of success because 75% of students have reached the KKM. student learning mastery increased by 70.58% (initial condition 8.82% increased to 70.58%). In the second cycle, with the improvement and modification of learning multimedia, accompanied by group formation management and giving rewards, student learning outcomes increased by 88.23% (the condition of the first cycle increased 70.58% to 88.23%). Learning achievement in cycle II has met the indicators of success because 75% of students have reached the KKM. student learning mastery increased by 70.58% (initial condition 8.82% increased to 70.58%). In the second cycle, with the improvement and modification of learning multimedia, accompanied by group formation management and giving rewards, student learning outcomes increased by 88.23% (the condition of the first cycle increased 70.58% to 88.23%). Learning achievement in cycle II has met the indicators of success because 75% of students have reached the KKM.